100%- you can see that the line in the middle goes from 3 to 24
Answer:
y = x² − 6x − 27
Step-by-step explanation:
To distribute, you can use something called FOIL. It stands for First, Outer, Inner, Last.
First, multiply the First term in each factor.
x · x = x²
Now multiply the Outer terms in each factor.
x · 3 = 3x
Next multiply the Inner terms in each factor.
-9 · x = -9x
Finally, multiply the Last terms in each factor.
-9 · 3 = -27
Add them all up:
x² + 3x − 9x − 27
x² − 6x − 27
Dude I don’t think using this for an exam is it but ok
Answer:
![2x^2-12x+5](https://tex.z-dn.net/?f=2x%5E2-12x%2B5)
Step-by-step explanation:
![(2x^2-3x+5)(x^2+4x+1)\\(2x^2-12x+5)](https://tex.z-dn.net/?f=%282x%5E2-3x%2B5%29%28x%5E2%2B4x%2B1%29%5C%5C%282x%5E2-12x%2B5%29)
Answer:
3 + 9i
Step-by-step explanation:
(4 + 2i) - (1 - 7i)
distribute the (-)
(4 + 2i) - 1 + 7i
combine like terms
3 + 9i